The Support of Innovation Activities in Rhône-Alpes - Czyżewska, Dorota (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Nowadays the activity of innovation support organizations seems important in the acquisition and diffusion of innovative solutions to the regional economies in order to build their competitive advantage. In the paper the socio-economic conditions of a French Rhône-Alpes region and the functioning of innovation support organizations in this region are developed. Then, some recommendations regarding the effectiveness of innovation support organizations in Rhône-Alpes are proposed; they can be useful also for Polish regions as best practices.